A topology analysis and genetic algorithm combined approach for power network intentional islanding. (October 2015) - Wu, Yingjun; Tang, Yi; Han, Bei; Ni, Ming
Highlights: A TA and GA combined approach for intentional network islanding is proposed. Vertices contraction can effectively simplify the large-scale power network. Removing redundant edges can reduce search space of line cutsets. Incorporating TA techniques into GA can effectively avoid infeasible solutions. The TAGACA can deal with weakly connected islands and predefined number of islands. Abstract: Intentional islanding is to determine proper network splitting strategy while ensuring local power balance and transmission capacity constraints when islanding operation is unavoidable. The intentional islanding problem is very complicated in general because a combinatorial exploitation of strategy space is required. This paper apply a topology analysis and genetic algorithm combined approach for determining proper splitting strategies of large-scale power networks. Topology analysis is used to simplify the original power network into a simple equivalent network so that the splitting strategy space world be dramatically reduced; while the genetic algorithm incorporated with the breadth-first search (BFS) is employed to determine the final proper splitting strategy in the simplified power network. Two additional applications, mimicking weak connections between islands and obtaining specific pre-defined islands, of the proposed method are introduced. Simulation results on several test system show that the proposed approach can quickly provide proper splitting strategies and is effective for larger-scale power systems.